2017
DOI: 10.1080/16549716.2017.1410975
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delayed initiation of breastfeeding: a survey in Northern Uganda

Abstract: Background: Initiation of breastfeeding later than 1 hour after birth is associated with increased neonatal morbidity and mortality. Objective: To determine the prevalence and factors associated with delayed initiation of breastfeeding. Methods: We conducted a survey in 2016 of 930 children under the age of 2 years in Lira district, northern Uganda. Mothers of the children were interviewed and data was collected on mobile phones using Open Data Kit software (https://opendatakit.org). Multivariable logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 31 publications
11
40
1
Order By: Relevance
“…There was strong evidence that birth by Caesarean section (CS) was associated with delay in initiation of breastfeeding. This was similar to findings from Uganda [ 30 ], Tanzania [ 31 ], Ethiopia [ 27 ], and Nigeria [ 32 ]. This could be explained by the hospital practice of separating infants from their mothers after CS as reported in studies in Nigeria [ 33 ] and Vietnam [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…There was strong evidence that birth by Caesarean section (CS) was associated with delay in initiation of breastfeeding. This was similar to findings from Uganda [ 30 ], Tanzania [ 31 ], Ethiopia [ 27 ], and Nigeria [ 32 ]. This could be explained by the hospital practice of separating infants from their mothers after CS as reported in studies in Nigeria [ 33 ] and Vietnam [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…The present study demonstrated that the newborn babies of uneducated parents were less likely to be breastfed within the first hour after birth. Note that several earlier studies [8,[27][28][29][30][31][32][33][34] have also found a similar effect of education; however, only mothers' level of education was considered in those studies, whereas education of both parents was considered in this study. The effect of education may be explained as educated parents have the ability to receive and understand health promotional information easily, and also they can manage the skilled or professional birth assistance or may take decision to go to health facilities during delivery [8].…”
Section: Discussionmentioning
confidence: 56%
“…[28,44,49,52,69]. The negative impact of caesarean delivery on early breastfeeding has also been observed in the several studies [8,28,29,34,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 25 27 34–36 41 Seven studies were conducted in Europe, 27 33–37 43 five in Middle East, 13 14 19 21 22 three in Africa, 20 25 41 one in Asia, 29 one study was conducted in both Asia and Europe 40 and one failed to report. 41 Nine studies reported on refugees, 13 14 19 21 25 32 37 40 43 four on internally displaced persons (IDPs), 20 22 34 36 three on non-displaced residents 27 29 41 and two failed to report on the target population. 35 42 Nine studies were conducted in camps, 13 14 19 21 25 32 37 40 43 seven in community 20 22 27 29 34 36 41 and two did not report.…”
Section: Resultsmentioning
confidence: 99%